2023
DOI: 10.1007/s00062-023-01291-1
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Artificial Intelligence for Abnormality Detection in High-volume Neuroimaging and Subgroup Meta-analysis for Intracranial Hemorrhage Detection

Abstract: Purpose Most studies evaluating artificial intelligence (AI) models that detect abnormalities in neuroimaging are either tested on unrepresentative patient cohorts or are insufficiently well-validated, leading to poor generalisability to real-world tasks. The aim was to determine the diagnostic test accuracy and summarise the evidence supporting the use of AI models performing first-line, high-volume neuroimaging tasks. Methods Medline, Embase, Cochrane li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…This step successfully overcame a significant obstacle often faced in brain age model development (i.e. identifying radiological normal scans in a large hospital dataset), resulting in a diverse and realistic set of training data that accurately represents clinical populations (Agarwal et al, 2023; Booth et al, 2023; Din et al, 2023). The diversity of our data, encompassing a range of scanner vendors, acquisition protocols, patient ethnicities, and a wide age span (18–96 years), added robustness to our models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This step successfully overcame a significant obstacle often faced in brain age model development (i.e. identifying radiological normal scans in a large hospital dataset), resulting in a diverse and realistic set of training data that accurately represents clinical populations (Agarwal et al, 2023; Booth et al, 2023; Din et al, 2023). The diversity of our data, encompassing a range of scanner vendors, acquisition protocols, patient ethnicities, and a wide age span (18–96 years), added robustness to our models.…”
Section: Discussionmentioning
confidence: 99%
“…However, realising this goal will involve overcoming several challenges. One challenge is the lack of representativeness of research datasets (Agarwal et al, 2023; Agarwal & Wood et al, 2023; Din et al, 2023), particularly public datasets commonly used for training brain age models. This applies not only to the demographics of the study participants, but also to the nature of the MRI data (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, in a theoretical “triage-based” Artificial Intelligence (AI) clinical pathway, a false-negative AI report (engendered by a low recall score for the model) may place the incorrectly-reported study to the bottom of the queue for human reporting and potentially significantly delay diagnosis. The exact definition of a “good enough” F1-score for neuroimaging applications remains to be determined and indeed, at the time of writing, almost no neuroimaging abnormality detection tools have been adequately validated in representative clinical cohorts ( 10 ), although there are a few notable exceptions ( 7 , 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…They can aid radiologists in the quantification and characterization of lesions, providing more accurate and reproducible measurements ( 133 ). Additionally, AI algorithms can help predict patient outcomes, such as the risk of recurrent strokes or response to treatment, based on imaging findings and clinical data ( 134 , 135 ). While, a study conducted by Voter AF and colleagues showed unexpectedly lower sensitivity and positive predictive values for Aidoc in diagnosing intracranial hemorrhage, which has raised concerns about the generalizability of these commercial AI tools ( 136 ).…”
Section: Future Directions and Conclusionmentioning
confidence: 99%